Learning Media Development Using Windows Movie Maker In The History Subject Of Grade XI High School - Wendy Ardiyanti; Sani Safitri; LR Retno Susanti (Criksetra: Jurnal Pendidikan Sejarah, 2019)
This research is entitled "Development of Learning Media Using Windows Movie Maker in the Subject of Class XI High School History". The problem is how to develop a valid historical learning media and effectiveness. The purpose of this study is to develop a valid and effective historical learning media in North Indralaya 2 High School. This research is a type of development research that uses the Alessi and Trollip development models including: planning, design, and development. The validity of the media is included in the valid category with a mean score of 3.87, the validity of the material is included in the valid category with an average value of 3.92, the validity of the learning design is included in the very valid category with an average value of 4.6. The potential impact of learning media using Windows Movie Maker can be seen from the increase in learning outcomes before and after using learning media. The mean value of the pretest obtained was 42.33 which was included in the low category while the posttest value obtained was 83.33. This shows that the learning media uses Windows movie maker with material on the events of the September 30 movement / Indonesian Communist Party that has valid values and effectiveness.